Effects of Daytime Dry Fasting on Hydration, Glucose Metabolism and Circadian Phase: A Prospective Exploratory Cohort Study in Bahá'í Volunteers - Koppold-Liebscher, Daniela A.; Klatte, Caroline; Demmrich, Sarah; Schwarz, Julia; Kandil, Farid I.; Steckhan, Nico; Ring, Raphaela; Kessler, Christian S.; Jeitler, Michael; Koller, Barbara; Ananthasubramaniam, Bharath; Eisenmann, Clemens; et al. (Frontiers in Nutrition, 2021)
Background: Religiously motivated Bahá’í fasting (BF) is a form of intermittent dry fasting celebrated by abstaining from food and drinks during daylight hours every year in March for nineteen consecutive days. Aim: To test safety and effects of BF on hydration, metabolism and circadian clock. Methods: Thirty-four healthy Bahá’í volunteers (15 women) participated in this prospective, exploratory cohort study. Laboratory examinations were carried out in four study visits: before fasting (V0), in the third week of fasting (V1) as well as three weeks (V3) and three months (V4) after fasting. Data collection included blood and urine samples, anthropometric measurements and bioelectrical impedance analysis. At V0 and V1, 24- and 12-hour urine and serum osmolality were measured. At V0 – V2, alterations in circadian clock phase were monitored in sixteen participants. Our study was augmented by an additional survey with 144 healthy Bahá’í volunteers filling out questionnaires and with subgroups attending metabolic measurements (n=11) and qualitative interviews (n=13), the results of which will be published elsewhere. Results: Serum osmolality (n = 34, p < 0.001) and 24-hour urine osmolality (n = 34, p = 0.003) decreased during daytime fasting, but remained within the physiological range and returned to their pre-fasting levels during night hours. BMI, total body fat mass and basal metabolic rate decreased significantly during fasting (n = 34, p < 0.001), while body cell mass and body water appeared unchanged. The phase of circadian rhythms advanced by 1.1 hrs (n = 16, p < 0.005) during fasting and returned to pre-fasting values three weeks after fasting. Most observed changes were not detectable anymore 3 months after fasting. Conclusions: Results indicate that BF is safe, has no negative effects on hydration, can improve fat metabolism and can cause transient phase shifts of circadian rhythms.